PENGARUH PENGGUNAAN BAHASA GAUL TERHADAP BAHASA INDONESIA BAKU DIKALANGAN MAHASISWA PGMI - Agis wildatun Agis wildatun tazkia (Jurnal Lazuardi, 2026)
This article aims to realize the influence of the use of slang on standard Indonesian among students of Elementary Madrasah Teacher Education (PGMI), the most influential use of slang in students' daily communication, both in direct communication and on social media, the research process carried out was observation and analysis of conversations between students. The results of this study prove that slang tends to be used to build closeness, familiarity, and statements of group identity. However, the superiority of slang also has an impact on decreasing students' ability to apply standard Indonesian in formal contexts, such as academic writing and presentations, this study concludes that the influence of slang use is very influential in the stability of standard language use. Therefore, efforts are needed to habituate the use of standard Indonesian in academic contexts through guidance and language training..